2012
DOI: 10.1038/labinvest.2011.193
|View full text |Cite
|
Sign up to set email alerts
|

Carbon tetrachloride-mediated lipid peroxidation induces early mitochondrial alterations in mouse liver

Abstract: Although carbon tetrachloride (CCl 4 )-induced acute and chronic hepatotoxicity have been extensively studied, little is known about the very early in vivo effects of this organic solvent on oxidative stress and mitochondrial function. In this study, mice were treated with CCl 4 (1.5 ml/kg ie 2.38 g/kg) and parameters related to liver damage, lipid peroxidation, stress/defense and mitochondria were studied 3 h later. Some CCl 4 -intoxicated mice were also pretreated with the cytochrome P450 2E1 inhibitor dieth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 50 publications
13
76
1
3
Order By: Relevance
“…Moreover, the Knockaert et al (38) study similarly found CCl 4 -mediated necrosis at 24 h (Fig. 4K and 7F), further supporting our hypothesis that early and extensive pro-apoptotic signaling leads to necrosis, or secondary necrosis, which have overlapping components (39).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the Knockaert et al (38) study similarly found CCl 4 -mediated necrosis at 24 h (Fig. 4K and 7F), further supporting our hypothesis that early and extensive pro-apoptotic signaling leads to necrosis, or secondary necrosis, which have overlapping components (39).…”
Section: Discussionsupporting
confidence: 87%
“…35) As shown in Table 3, CPE was effective in preventing CCl 4 -induced CYP2E1 mRNA degradation, which is in agreement with the previous report showing that cacao polyphenol metabolites acted as potent inhibitors of CYP2E1 activity. 36) The inhibitory effects of CPE on CYP2E1 activity may provide an explanation for CPE antioxidant properties against CCl 4 -induced oxidative stress beyond its capacity to scavenge CCl 4 -induced radicals directly, although further work is required to establish the causal relationship between CPE and PCOOH, MDA, GPx, and CYP2E1 activity.…”
Section: -Induced Oxidative Stress and Its Amelioration By Cpesupporting
confidence: 91%
“…4,20) Moreover, CCl 4 is a prototypical lipid peroxidant that induces early lipid peroxidation in the liver. 8) As a marker of lipid peroxidation, MDA concentration was measured in all animal groups. CCl 4 treatment significantly increased MDA levels, whereas pretreatment with JTX eliminated CCl 4 -induced MDA upregulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, associated protective mechanisms possibly act on each of the five steps. [7][8][9][10] The Japanese herbal medicine "Juzen-taiho-to" (JTX) is a Kampo medicinal prescription, and has been used historically in Japan for the treatment of cancers, rheumatoid arthritis, and atopic dermatitis. 11) JTX is consisting of ten medicinal herbs in the indicated amounts (g per day in human intake);…”
mentioning
confidence: 99%